Family physicians have greater ambiguity tolerance in the clinical context: A nationwide cross‐sectional study - Hirohisa Fujikawa; Takuya Aoki; Takayuki Ando; Junji Haruta (Journal of General and Family Medicine, 2025)
Abstract Background Ambiguity tolerance in the clinical context is increasingly recognized as essential for physicians to work as professionals. However, the relationship between specialty and ambiguity tolerance in the clinical context has been understudied. Here, we investigated the association between specialty and ambiguity tolerance in the clinical context, focusing on differences between family physicians (FPs) and non‐FPs. Methods We performed a nationwide cross‐sectional study in Japan. We asked FPs from 14 family medicine residency programs across Japan and non‐FPs from monitors of an internet survey company in Japan to participate in the study. We assessed their tolerance for ambiguity using the Japanese version of the Tolerance for Ambiguity in Medical Students and Doctors (J‐TAMSAD) scale. Results In total, 388 physicians (178 FPs and 210 non‐FPs) completed our anonymous online survey and were included in the analysis. After adjustment for possible confounders (gender and postgraduate years), FPs had higher J‐TAMSAD scale scores than internists/pediatricians, surgeons, and physicians with other specialties, meaning that FPs had greater ambiguity tolerance. Conclusions This study reveals that FPs had greater tolerance for ambiguity in the clinical context than non‐FPs. Our findings suggest that there may be a need to increase non‐FP's tolerance for ambiguity specific to the clinical context through educational interventions, since ambiguity is inherent and growing in medicine today. FPs and non‐FPs should work together to complement each other's strengths, rather than simply improving the training of non‐FPs.